Οι επετειακές σχολικές εκδηλώσεις: διδακτική της ιστορίας σε ιδεολογικό πεδίο - Γκόλια, Παρασκευή; Αναστασιάδου, Σοφία (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
In this paper, we chose to examine the standardized speeches of the educational authorities for the national celebrations during the years 1924 to 2007, aiming to depict, not only the ideological function it fulfils, but also their connection to school history. The method selected is the implicative analysis according to R. Grass. The analysis of the data showed that in annual celebration speeches we run across ideas which express stereotypes and prejudice views, nationalistic ideas, twisted images of neighboring countries, intolerant aspects for different cultures. In general, we observe that annual celebration speeches describe and analyze historical events, which are taught to elementary students at the subject of history, depicting the parameters of a constructed collective memory and national identity. It is obvious that the contemporary Greek school requires a new orientation and strategy on behalf of the teacher’s in order to construct a harmonic, school community because the cross-cultural aspect and the pedagogy for peace is absent since the value of the diversity of annual celebration speeches is not presented as the primary principle on which other cultural groups can be treated as equals.